Inhibitory activity of cyclohexenyl chalcone derivatives and flavonoids of fingerroot, Boesenbergia rotunda (L.), towards dengue-2 virus NS3 protease - Tan, Siew Kiat; Pippen, Richard; Yusof, Rohana; Ibrahim, Halijah; Khalid, Norzulaani; Abd Rahman, Noorsaadah (Elsevier, 2006)
Boesenbergia rotunda (L.) cyclohexenyl chalcone derivatives, 4-hydroxypanduratin A and panduratin A, showed good competitive inhibitory activities towards dengue 2 virus NS3 protease with the K-i values of 21 and 25 mu M, respectively, whilst those of pinostrobin and cardamonin were observed to be non-competitive. NMR and GCMS spectroscopic data formed the basis of assignment of structures of the six compounds isolated. (c) 2006 Elsevier Ltd. All rights reserved.